2022
DOI: 10.1002/oby.23396
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relationship of baseline functional brain networks with intentional weight loss in older adults

Abstract: Objective:The goal of this study was to determine whether the degree of weight loss after 6 months of a behavior-based intervention is related to baseline connectivity within two functional networks (FNs) of interest, FN1 and FN2, in a group of older adults with obesity.Methods: Baseline functional magnetic resonance imaging data were collected following an overnight fast in 71 older adults with obesity involved in a weight-loss intervention. Functional brain networks in a resting state and during a food-cue t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…Following brief postabsorptive states, we have found that brain networks both in the resting state and in response to active imagery of desired food are associated with 6-month weight loss. 34 An interesting question for future research is whether these effects are moderated by decline in EF and other cognitive domains common to aging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following brief postabsorptive states, we have found that brain networks both in the resting state and in response to active imagery of desired food are associated with 6-month weight loss. 34 An interesting question for future research is whether these effects are moderated by decline in EF and other cognitive domains common to aging.…”
Section: Discussionmentioning
confidence: 99%
“…We recently conducted a second, longitudinal study to examine whether connectivity metrics at baseline in these two functional networks were related to 6-month weight loss, the end of the intensive phase of treatment. 34 During the baseline resting state scan, the relationship of functional connectivity and network clustering in FN1 was significantly associated with 6-month weight loss. It is important to recall that this network involves both unconscious sensory, motor, cognitive, and affective processes that are likely responsible for the intrusive quality of food craving, and conscious cognitive and affective processes that serve to elaborate on these intrusive cues fueling the desire for food consumption, a position consistent with Kavanagh's Elaborated Intrusion Theory of Desire.…”
Section: Exploration Of Fn1 and Fn2 In An Independent Study Of Weight...mentioning
confidence: 92%
See 1 more Smart Citation
“…The PoCG is the primary somatosensory cortex and conveys sensory information to the hippocampus, contributing to food intake regulation (Kanoski & Grill, 2017). Evidence from recent longitudinal studies have demonstrated that activities in the hippocampus and somatosensory were linked with future BMI of adolescents and older adults (Burdette et al, 2022;Park et al, 2020). Based on larger neuroimaging datasets, our recent multivariate resting-state functional connectome-based prediction study also suggested that dysfunctions in the sensory and reward regions that involved in encoding food cues may act as reproducible biomarkers of obesity (Wang et al, 2023).…”
Section: Hippocampus Connectivity Predicts Future Bmi and Eatingmentioning
confidence: 99%